Text-oriented research into interpreting - Examples from a case-study - Lamberger-Felber, Heike (HERMES - Journal of Language and Communication in Business, 2001)
Different methodological tools were applied in a case study on interpretation of read-out speeches: A comparison of the 3 source texts used showed considerable differences between the „objective“ text description using quantifiable parameters and the „subjec-tive“ evaluation of the same speeches by the 12 participating interpreters. Incorrect rendition or omission of proper names/numbers was reduced by the use of the manuscript in the booth, while overall omissions/errors were highly variable between subjects. In a process-oriented approach, the relationship between use of manuscript, timelag and long omissions was studied and resulted in a series of new questions to be investigated. Finally, lexical variability proved surprisingly high with only 6.6% of words being used by all interpreters. Strengths and weaknesses of the different methodological tools will be discussed and proposals made for further research in the field.